A RELICT-GRAIN-BEARING PORPHYRITIC OLIVINE COMPOUND CHONDRULE FROM LL3.0 SEMARKONA THAT EXPERIENCED LIMITED REMELTING - Rubin A.E. (My University, 2006)
Chondrule D8n in LL3.0 Semarkona is a porphyritic olivine (PO) chondrule, 1300 × 1900 μm in size, with a complicated thermal history. The oldest recognizable portion of D8n is a moderately high-FeO, PO chondrule that is modeled as having become enmeshed in a dust ball containing a small, intact, low-FeO porphyritic chondrule and fine-grained material consisting of forsterite, kamacite, troilite, and possibly reduced C. The final chondrule melting event may have been a heat pulse that preferentially melted the low-FeO material and produced a low-FeO, opaque-rich, exterior region, 45-140 μm in thickness, around the original chondrule. At one end of the exterior region, a kamacite- and troilite-rich lump 960 μm in length formed. During the final melting event, the coarse, moderately ferroan olivine phenocrysts within the original chondrule appear to have been partly resorbed (These relict phenocrysts have the highest concentrations of FeO, MnO, and Cr 2 O 3 - 7.5, 0.20, and 0.61 wt%, respectively - in D8n.). Narrow olivine overgrowths crystallized around the phenocrysts following final chondrule melting; their compositions seem to reflect mixing between melt derived from the exterior region and the resorbed margins of the phenocrysts. During the melting event, FeO in the relict phenocrysts was reduced, producing numerous small blebs of Nipoor metallic Fe along preexisting curvilinear fractures. The reduced olivine flanking the trails of metal blebs has lower FeO than the phenocrysts but virtually identical MnO and Cr 2 O 3 contents. Subsequent parent-body aqueous alteration in the exterior region of the chondrule formed pentlandite and abundant magnetite. © The Meteoritical Society, 2006.